Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.32598/ppj.24.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba modulates hippocampal BDNF expression in a rat model of chronic restraint stress-induced depression

Abstract: Introduction: Mood disorders such as depression and anxiety disorders have been affecting a relatively high proportion of the world's population. Neuroplasticity hypothesis of depression proposes that lack of brain-derived neurotrophic factor (BDNF) can cause structural changes in the brain. The extract of Ginkgo biloba (Gb) leaves can restore much of the damage in the nervous system. We examined the antidepressant role of Gb extract (EGb 761) on BDNF expression modulation in the hippocampus of rats subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
(73 reference statements)
0
1
1
Order By: Relevance
“…Regarding body weight, CRS did not cause any change in body weight of rats on days 7, 14 and 21 of the present study compared to the control group. However, previous studies reported decrease in body weight of rats exposed to CRS in comparison to control rats [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Such contradiction between our study and other studies could be because the 21-day stress paradigm used in our study could not cause profound hypothalamic damage that may become evident with longer stress durations.…”
Section: Discussioncontrasting
confidence: 88%
“…Regarding body weight, CRS did not cause any change in body weight of rats on days 7, 14 and 21 of the present study compared to the control group. However, previous studies reported decrease in body weight of rats exposed to CRS in comparison to control rats [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Such contradiction between our study and other studies could be because the 21-day stress paradigm used in our study could not cause profound hypothalamic damage that may become evident with longer stress durations.…”
Section: Discussioncontrasting
confidence: 88%
“…Compared with control groups, pretreatment with 30 and 60 mg/kg/day GBE substantially reduced depressive-like effects in RSS rats and prevented changes in DNA methylation and protein expression of the brain-derived neurotrophic factor (BDNF) in the hippocampus induced by persistent stress. ese results indicate that GBE may exert antidepressant effects by modulating BDNF expression in the hippocampal nucleus [121].…”
Section: Antidepressant Effectsmentioning
confidence: 75%